MON-LB100 Novel Paradoxical Markers of Weight Loss: Is the Worse Actually the Better? a Retrospectiveanalysisof 1,567 Patientswith Obesity With Successful Clinical Weight-Loss Approaches - Cadegiani, Flavio (J Endocr Soc, 2020)
Background:Obesity is a chronic, multi-factorial, and relapsing disorder that has been reported to be a risk factor to more than 200 diseases, among which the majority is direct- or indirectly triggered by the metabolic abnormalities induced by excessive body fat. Indeed, patients with obesity tend to disclose multiple alterations of metabolic markers, which tend to improve with weight loss. Despite the multiple dysfunctions extensively in this population, only mandatory biochemical exams are usually ordered, likely due to limitations in cost and lack of cost-effectiveness, since the majority of the parameters typically altered in obesity does not drive therapeutic choices or influence in an individual-based evaluation.We developed a protocol for obesity treatment that includes a thorough analysis and follow up of the biochemical parameters of patients with obesity, including more than 50 parameters, for more precise diagnosis and response to treatments. Among these parameters, we identified unexpected changes, including some that would initially be related to increased cardiovascular risk or worse prognosis when in an usual context, but which could peculiarly indicate successfulness of weight loss, since these parameters tend to return to normal levels after a period in the new body weight. Our objective is to identify whether these paradoxical changes in biomarkers are linearly correlated with body weight loss, fat loss, mass loss, or whether they were related to the use of any anti-obesity drug. Methods: In a retrospective cohort of 1,567 patients that underwent a clinical weight loss treatment for obesity in a obesity center (Corpometria Institute, Brasília, DF, Brazil), we performed a linear association analysis between body weight and body fat (air displacement pletismography - Bod Pod, CosMed, USA) and 65 parameters, including hormonal, metabolic, inflammatory, and immunologic parameters. We also adjusted for the use of anti-obesity drugs. Results: Homocysteine and triglycerides were identified to increase linearly according to the amount of weight loss (r = -0.77) and fat loss (r = -0.85), but not due to the use of any drug. Folic acid decrease was directly related to fat loss (r = 0.81). Additional findings include more significant decrease of ApoB, compared to LDLc, decreases of GGT, ALT, CRP, ESR, neutrophils, ferritin, fibrinogen, PTH, free T3, uric acid, a and temporary decrease of ApoA and HDLc, all related with body fat loss. Conclusions: Increase of homocysteine resulted from decreased folic acid metabolism, and increased triglycerides may be indirect markers of lipolysis, as no other plausible mechanism could explain these findings.